Occurrence and Multilocus Genotyping of Giardia duodenalis in Yunnan Black Goats in China. (10th October 2018) - Xie, Shi-Chen; Zou, Yang; Chen, Dan; Jiang, Meng-Meng; Yuan, Xiao-Dan; Li, Zhao; Zou, Feng-Cai; Yang, Jian-Fa; Sheng, Jin-Liang; Zhu, Xing-Quan
Abstract : Giardia duodenalis is an important zoonotic parasite which can parasitize in the intestines of humans and various animals . However, the information about the prevalence and genetic diversity of G. duodenalis in goats in China is limited. It is yet to be known whether Yunnan black goats, a unique goat breed in subtropical Yunnan province, southwestern China, are infected with G. duodenalis. Thus, a total of 907 fecal samples were collected from Yunnan black goats in five regions in Yunnan province, to estimate the prevalence and genotypes of G. duodenalis using a PCR-based approach. The G. duodenalis prevalence is 4.2% (38/907) in Yunnan black goats by nested amplification of the β -giardin (bg) gene, and the genotypes are identified as assemblage E, with 5 novel subtypes (E11 -E15 ). Multilocus sequence typing revealed that 11, 18, and 38 samples were amplifiable on tpi (triose phosphate isomerase), gdh (glutamate dehydrogenase), and bg locus, respectively, and identified three novel multilocus genotypes (MLGs): MLGE9-MLGE11. To our knowledge, this is the first report of G. duodenalis prevalence and genotypes in Yunnan black goats in China, which extended the host range of G. duodenalis and provided basic data for controlling G. duodenalis infection in Yunnan black goats.